1998
DOI: 10.1002/etc.5620170428
|View full text |Cite
|
Sign up to set email alerts
|

Predicting toxicity in marine sediments with numerical sediment quality guidelines

Abstract: Matching synoptically collected chemical and laboratory bioassay data (n = 1,068) were compiled from analyses of surficial sediment samples collected during 1990 to 1993 to evaluate the predictive ability of sediment quality guidelines (SQGs), specifically, effects range—low (ERL), effects range—median (ERM), threshold effects level (TEL), and probable effects level (PEL) values. Data were acquired from surveys of sediment quality performed in estuaries along the Atlantic, Pacific, and Gulf of Mexico coasts. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
254
5
9

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 704 publications
(276 citation statements)
references
References 18 publications
(52 reference statements)
8
254
5
9
Order By: Relevance
“…Between a proportion of 0.05 and 0.2 of the PECs exceeded, 40% of the samples were toxic to H. azteca. Consistent with these results, Long and MacDonald (1998) reported low probability of toxicity (12%) below a mean ERM quotient of 0.1 and a high probability of toxicity (74%) above a mean ERM quotient of 1.5 in sediment toxicity tests with marine amphipods. Similarly, MacDonald et al (2000a) report an incidence of toxicity of Ͼ85% at a mean PEC quotient above 0.5 for a variety of freshwater sediment tests.…”
Section: Comparison Of Sediment Characteristics To Toxicity Responsessupporting
confidence: 85%
See 1 more Smart Citation
“…Between a proportion of 0.05 and 0.2 of the PECs exceeded, 40% of the samples were toxic to H. azteca. Consistent with these results, Long and MacDonald (1998) reported low probability of toxicity (12%) below a mean ERM quotient of 0.1 and a high probability of toxicity (74%) above a mean ERM quotient of 1.5 in sediment toxicity tests with marine amphipods. Similarly, MacDonald et al (2000a) report an incidence of toxicity of Ͼ85% at a mean PEC quotient above 0.5 for a variety of freshwater sediment tests.…”
Section: Comparison Of Sediment Characteristics To Toxicity Responsessupporting
confidence: 85%
“…The proportion of PECs exceeded was also calculated for each sediment sample from Waukegan Harbor and for sediment toxicity tests reported for H. azteca by Ingersoll et al (1996; n ϭ 62 samples), Kemble et al (1998;n ϭ 49 samples), and Ingersoll et al (1998;n ϭ 18 samples). A mean PEC quotient was calculated for each of these samples by first dividing the concentration of an individual chemical by its respective PEC, summing each of these individual values, and dividing the sum by the number of PECs for that sample Ingersoll et al 1998;Long et al 1998;MacDonald et al 2000a). A total of 149 sediment samples were evaluated in this historical database, and 32% of these samples were designated as toxic.…”
Section: Comparison Of Sediment Characteristics To Toxicity Responsesmentioning
confidence: 99%
“…To estimate the toxicity of trace metals in the estuarine sediment of the Souss River, we have used the ranges of concentrations that Long et al (1995Long et al ( , 1998 and MacDonald et al (2000) have reported for each metal, determining its toxicity towards benthic organisms. Under these conditions, the annual values recorded for Cd, Cr, Hg, Pb, and Zn, were under the guidelines proposed by these authors (Table 4), so that their toxicological effects were low or non-existent.…”
Section: Except a Questionable Ni Concentration Inmentioning
confidence: 99%
“…So the impact of pollution caused by domestic wastewater in the Souss estuary was low in 2001 as well as in 2003. Long et al (1998) to characterise the toxicity of a metal (lg.g -1 ) in an estuarine sediment towards benthic organisms …”
Section: Except a Questionable Ni Concentration Inmentioning
confidence: 99%
“…Daskalakis et al, 1995;Long et al, 1998;Ishiga et al, 2000a). Okinawa Island has been of interest to many geochemical studies over the past years (eg.…”
Section: Introductionmentioning
confidence: 99%